Implementasi Manajemen Rantai Pasokan Anggrek terhadap Atribut Kualitas Pelayanan dan Produk pada Duta Orchid Sanur, Bali - ZEFANYA, THALIA RATU; ANTARA, MADE; SUDARMA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Implementation of the Supply Chain Management of Orchid to Service and Product Quality Attributtes in Duta Orchid Sanur, Bali. Orchid is one of the potential ornamental plants that are developed because it is popular among the community and is in great demand by consumers. Since 2007 Duta Orchid is one of the best orchid centers in Bali. Seeing these conditions, the authors want to know about: (1) Conditions of orchid supply chain management conditions which include chain structure, chain targets, chain management, chain resources and supply chain business processes. (2) Assessments that consumers feel about the quality of service attributes and Duta Orchid products that are related to the implementation of orchid supply chain management.The results of the study show that: (1) Management of the orchid supply chain at Duta Orchid which involves suppliers, orchid agents, florists, and end consumers as a whole runs in an integrated manner as seen from product flow, money flow, and information flow that runs smoothly. (2) An assessment of the service and product quality attributes perceived by Duta Orchid consumers is related to the implementation of supply chain management, the attributes that must be maintained are plant prices, durability, employee friendliness, employee accuracy, complaint handling, service speed, and convenience. transactions, while the attributes that must be improved are variations in orchids and supporting facilities in the Duta Orchid. Then the last, attributes that have a low priority but still need to be considered are the availability of guarantees, location, plant layout, media promotion, and availability of information.Suggestions that can be used as input for Duta Orchid, namely Duta Orchid must maintain good and smooth supply chain management. In addition, Duta Orchid should focus on the attributes in the quadrant I. Another thing is Duta Orchid also need to consider the performance of the attributes located in quadrant III if it can have a good impact on Duta Orchid if its performance is improved.